Territorial Court House - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Territorial Court House in Dawson, Yukon Territory. Designed by architect Thomas W. Fuller this building is now listed on the Canadian Register of Historic Places under "Former Territorial Court House."